PERAN GURU PPKn DALAM MENGATASI DEGRADASI MORAL PESERTA DIDIK DI SEKOLAH SMAN 2 PALEMBANG - Fadhilah, Naurah; El Faisal, Emil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
study aims to examine the role of Civic Education (Pancasila and Citizenship Education) teachers in addressing the moral degradation of students at SMAN 2 Palembang. This research is expected to provide a comprehensive overview of the role of Civic Education teachers in instilling moral values and contributing to the development of more positive student behavior. The study highlights the rapid development of the times and advances in technology, which have led to the emergence of behaviors indicating a decline in moral values within the school environment. This situation poses a particular challenge for Civic Education teachers in instilling moral values and shaping students’ character. This research employs a qualitative approach with a descriptive method. Data were collected through triangulation techniques, including observation, interviews, and documentation. The research subjects consisted of Civic Education teachers, the vice principal for student affairs, and students. The collected data were analyzed through data reduction, data presentation, and conclusion drawing. The results of the study indicate that Civic Education teachers at SMAN 2 Palembang have performed their roles optimally as motivators, friendly communicators, and mentors in addressing students’ moral degradation. The cultivation of moral values is carried out by integrating Pancasila values into every Civic Education learning material. Values such as honesty, discipline, responsibility, tolerance, and democratic attitudes are instilled through discussions, case studies, and reflections on events occurring in the surrounding environment. Civic Education teachers also provide role models in daily school life by acting fairly, respecting differences, and demonstrating behavior that aligns with moral values. These efforts have been shown to foster moral awareness and encourage positive behavioral changes among students